Influence of sugar cane molasses on growth of nitrogen fixing bacteria (Stenotrophomonas maltophilia) and rice yield - Hashim, Noor Hidayah (2016)
Sugar cane molasses is an important carbon source for the growth of nitrogen fixing bacteria. Nitrogen fixing bacteria utilize root exudate carbon compound and form association with plant and fix nitrogen. Sugar cane molasses as an external carbon sources for nitrogen fixing bacteria is low-cost efficient growth factor. Thus, addition of sugar cane molasses to the rice plant may be able to provide carbon substrate to nitrogen fixing bacteria and also improved rice yield parameter. A series of experiments were conducted in the laboratory and glasshouse conditions with the following objectives: 1) To determine the effect of different concentrations of molasses on growth of Stenotrophomonas maltophilia (Sb16) in culture media incubation and soil amended with molasses and urea N, 2) To determine the effect of sugar cane molasses on growth of N2-fixing bacteria and effect of S. maltophilia (Sb16) and molasses and urea-N on total starch, total sugar and rice yield and to elucidate their distribution of N partitioning in the plant parts. Laboratory and glasshouse experiments were arranged in a factorial experiments in complete randomized design (CRD) with 3 replication and factorial completely randomized design (RCBD) with 4 replications using SAS statistical program version 9.3. In the glasshouse study, each block consist of 2 bacterial treatments: control (0) and Stenotrophomonas maltophilia (Sb16), 3 amendments treatment: control (0), urea application (60 kg N ha-1) and molasses application (2 tan ha-1). Mean separation was carried out using Tukey's Studentized Range (HSD) at the 5% level of probability. An experiment was conducted to test the growth of Stenotrophomonas maltophilia (Sb16) on different media in laboratory and consecutively test the growth of S. maltophilia (Sb16) on soil. The different media for S. maltophilia growth was made by adding molasses as carbon (C) sources, compared to commonly used Nutrient broth and Trypic Soy broth. In the soil incubation study molasses and urea were added to soil inocculated with S. maltophilia (Sb16). A glasshouse study was conducted to determine the effect of N2 fixing bacteria, S. maltophilia (Sb16) and sugar cane molasses on total starch and total sugar and growth of rice. Two rates of sugar cane molasses (0 and 2 tan ha-1), urea (0 and 60 kg N ha-1) and S. maltophilia (Sb16) were applied to MR 219 rice variety. Plant growth and yield, total starch and sugar, N uptake and biomass of plants were determined. The highest growth of S. maltophilia strain Sb16 (14.84 mg mL-1) was observed at sugarcane molasses concentration of 20% w/v at 24 hour incubation. Total reducing sugar increased with increasing molasses concentrations. High total N (505 mg L-1) was produced in 7.5% w/v molasses concentration. Application of urea significantly influenced total population and total reducing sugar of S. maltophilia (Sb16). Highest of total bacterial population (7.97 log10 cfu dry weight soil-1) and total reducing sugar (0.098 mg g-1 glucose) were observed in urea treatment at day 7. While, application of molasses significantly increased total N (0.31%) in the soil applied with S. maltophilia (Sb16). Application of molasses to uninoculated MR 219 rice significantly increased tiller plant-1, aboveground dry matter, grain yield, 100-grain weight, straw yield, harvest index (HI) and biological yield. Application of molasses and urea to rice plant inoculated with S. maltophilia (Sb16) significatly increased grain yield, with application of molasses also showed significantly increased grain weight and aboveground dry matter compared to inoculated plants. Highest tiller number plant-1, aboveground dry matter, grain yield, HI and biological yield were observed in application molasses with uninoculated MR 219 rice plant. High N content and N uptake in leaf blade were observed with uninoculated plant applied with molasses. Application of molasses to inoculated plants showed high total sugar of leaf blade and leaf sheath of rice plant. While, application of molasses to uninoculated plants resulted in high total sugar of stem, panicle and grain. Application of molasses to uninoculated plants showed high total starch in leaf blade, leaf sheath, panicle and grain, while, application molasses to inoculated plants was observed to produce high total starch in stem. The results suggested that sugar cane molasses can provide carbon source and increase S. maltophilia (Sb16) growth and yeild parameters of rice.